The Effect Of Yoga Exercise On Depression In Menopausal Women In Babakan Sari Sub-District, Bandung City - Sri Hayati; Sansuwito, Tukimin Bin; Irawan, Erna (International Journal of Health Sciences, 2023)
Women experience menopause, which is the cessation of menstruation for more than one year and the cessation of the release of the hormone’s estrogen and progesterone. The most common psychological impact of menopause is depression. Interventions that can be performed on depression include pharmacological and non-pharmacological methods. One of the non-pharmacological therapies is yoga. Yoga exercise involves the unification of body movement, breath, and mind. Most women aged >45 live in the Babakan Sari Sub-District. This study aimed to determine the effectiveness of yoga exercises in reducing depression in menopausal women in the Babakan Sari Sub-District.This study uses a quasi-experimental design with one group intervention. The population of this study was women >45 years in the Babakan Sari Sub-District, totaling 3225 people. Samples were taken using purposive sampling with the inclusion criteria of menopausal women who had partners, and the exclusion criteria were menopausal women who consumed depression medication totaling 50 people. Data collection was done using the Patient Health Questionnaire-9. Yoga intervention based on yoga practice SOP was given 3 times in 3 weeks. Univariate data analysis was done using percentages and bivariate using a t-test. The results showed that at the pretest, 25 people (50%) were experiencing moderate depression, 18 people (36%) met the criteria for mild depression, and 7 people (14%) met the criteria for mild depressive symptoms. Posttest results showed that 19 people (38%) had mild depression, 23 people (46%) met the criteria for mild depressive symptoms, and 8 people had no symptoms of depression (16%). The results of the t-test showed that p-value = 0.00 < a = 0.05. Thus, yoga exercises are effective in reducing depression in menopausal women. The results show that yoga exercises are effective in reducing depression because yoga exercises provide relaxation for menopausal women, with interventions given every 3 times a week for 3 weeks, increasing the effectiveness of yoga in reducing depression. Depression decreases after giving yoga exercises, so it is hoped that yoga exercises can be considered as an alternative intervention by health centers.